Power Management of Grid Connected Hybrid PV/Wind/Battery Power System - Ranjith Kumar, K.; M.Surya Kalavathi, Dr. (International Journal of Engineering and Technology, 2018)
The ever increasing energy demand and depletion of fossil fuels creates an importance in renewable energy systems. Photovoltaic (PV) and wind are the two prominent sources among the different available renewable energy sources. But due to intermittent nature of these sources the power system network may not be reliable. Therefore a hybrid power system (HPS) is the best solution to overcome this drawback. The main challenging task in HPS is coordination among the different sources. The HPS should achieve the power balance between the supply and demand under all the varying weather conditions like temperature, irradiation and wind speed. The aim of this paper is to design an optimal power management strategy for the renewable energy based hybrid power system (HPS). In HPS, PV and wind are used as the primary energy sources and battery is used as the energy storage system. In this work Genetic Algorithm (GA) is used for power management of HPS. The hybrid power system has been simulated using MATLAB using practical load and weather data of PV and wind system: which gives better performance under all operating conditions